Mechanical circulatory support in refractory cardiogenic shock due to influenza virus-related myocarditis. Issue 3 (3rd September 2020) - Sieweke, Jan-Thorben; Akin, Muharrem; Stetskamp, Sebastian; Riehle, Christian; Jonigk, Danny; Flierl, Ulrike; Pfeffer, Tobias J.; Hirsch, Valentin; Dutzmann, Jochen; Hoeper, Marius M.; Kühn, Christian; Bauersachs, Johann; et al.
Background: There is scarce evidence for mechanical circulatory support (MCS) in patients with influenza-related myocarditis complicated by refractory cardiogenic shock (rCS). We sought to investigate the impact of MCS using combined veno-arterial extracorporeal membrane oxygenation (VA-ECMO) and micro-axial flow pumps (the ECMELLA concept) in influenza-related myocarditis complicated by rCS. Methods: This is a prospective, observational analysis from the single centre HAnnover Cardiac Unloading REgistry (HACURE) from two recent epidemic influenza seasons. We analysed patients with verified influenza-associated myocarditis complicated by rCS who were admitted to our intensive care unit (ICU) on MCS. Subsequently, we performed a propensity score (PS) matched analysis to patients with acute myocardial infarction (AMI) complicated by rCS and non-ischaemic cardiomyopathy (DCM) related rCS. Results: We describe a series of seven patients with rCS-complicated influenza-related myocarditis (mean age 56±10 years, 58% male, influenza A (n=2)/influenza B (n=5)). No patient had been vaccinated prior to the influenza season. MCS was provided using combined VA-ECMO and Impella micro-axial flow pump. In two patients with out-of-hospital cardiac arrest, VA-ECMO had been implanted for extracorporeal cardiopulmonary resuscitation. All patients died within 18 days of hospital admission. By PS-based comparison to patients with AMI- or DCM-related rCS and combined MCS, 30-day mortality was significantly higher in influenza-related rCS. Conclusion: Despite initial stabilisation with combined MCS in patients with rCS-complicated influenza-related myocarditis, the detrimental course of shock could not be stopped and all patients died. Influenza virus infection potentially critically affects other organs besides the heart, leading to irreversible end-organ damage that MCS cannot compensate for and, therefore, results in a devastating outcome. Combined mechanical circulatory support in refractory cardiogenic shock (ECMELLA) might not salvage patients with influenza-associated myocarditis and severe end-organ damage, in contrast to the favourable effects in primary cardiac causes https://bit.ly/3dmonC4